The Interplay Between Thematic Resolution, Forest Cover, and Heterogeneity for Explaining Euglossini Bees Community in an Agricultural Landscape - Carneiro, Lázaro da Silva; Aguiar, Willian Moura de; Priante, Camila de Fátima; Ribeiro, Milton Cezar; Frantine-Silva, Wilson; Gaglianone, Maria Cristina (Frontiers in Ecology and Evolution, 2021)
Human activities have modified the landscape composition. The changes in the landscape structure can be evaluated by metrics, which are influenced, among other factors, by the number of cover classes used for the landscape classification (thematic resolution). In high thematic resolutions, landscape covers that can influence biological responses are identified and detailed. In low thematic resolutions, this detail level is lower because it aggregates different landscape covers in a few classes. However, how the thematic resolution influences our ability to understand landscape structure on biodiversity is poorly explored, particularly for pollinators. Here we asked how thematic resolution affects the explanatory power of landscape composition on explaining Euglossini bees (richness and abundance) within 15 landscapes composed mainly of coffee and pasture. To address this issue, we quantified the association between five attributes of the euglossine bee community and landscape composition attributes: landscape cover classes (%) and landscape heterogeneity. Moreover, we also evaluated how the thematic resolution influences bee responses to landscape structure. We found a strong and positive influence of landscape heterogeneity in low thematic resolutions (i.e. few cover classes on maps) over the richness and rare species abundance. We also observed that- in addition to the forest cover in the landscape- the pasture cover (%) quantified in high thematic resolution positively influenced the total abundance and abundance of common and intermediate species. Our study highlights the importance of maintaining compositional heterogeneity for the orchid bee community in agroecosystems, and forest cover for the biological requirements and conservation of these pollinators. Moreover, the use of different thematic resolutions showed how specific types of landscape covers influence the euglossine community attributes. This can highlight the species preferences for habitats and landscape covers. Thus, we call the attention of landscape ecologists to the importance of the definition of thematic resolution, as our ability to quantify the association between biological responses and landscape structure may be influenced by the number of classes used when building thematic maps.